Synergy of Islamic Work Ethic (IWE) and Maslahah to Reconstruct Evaluation of Islamic Bank Performance - Maharani, Satia Nur; Ayu Rahmawati, Setya; ., Syihabudin (KnE Social Sciences, 2020)
Reconstructing the fundamental values of the Islamic is an important part of improving its performance. The goal of Islamic Bank should not only be considered from materialist perspectives but also from a more spiritual viewpoint. The role of social, mental and spiritual considerations in achieving prosperity must also be acknowledged and evaluated. For this reason, synergy between the Islamic Work Ethic (IWE) and maslahah can be used to construct a performance evaluation that can be used alongside or even instead of conventional measurement. Keywords : Islamic Work Ethic (IWE), Maslahah, Performance Evaluation